The general overview of organic market structure, foreign trade and regulation in Turkey and the EU - Sayin C.; Mencet M.M. (The market for organic products in the Mediterranean region, 2003)
Since the beginning of the past decade, organic agriculture has gained huge importance in the world. The increasing domestic market demand in developed countries such as the USA, Canada, Austria, Japan, EU and the export potential in developing countries have stimulated organic agriculture. Currently, organic products are produced in more than 130 countries around the world. There is a large number of organic products composed of plant and animal product as well as several processed food and juices. Trade capacity of organic processed food is gradually expanding. The share of the organic food market compared with the conventional food market is small in ail countries. However, the market size and share of organic products varies from country to country. Turkey is considered as one of the important countries in the world in terms of organic production. In this paper, the developments of the organic market, and foreign trade and regulations of Turkey and EU are examined.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)